(untitled) (Research, Society and Development, 2024)
The technique of concept mapping fosters both personal and collective autonomy by promoting promoting the exercise of various cognitive skills, which favor creativity and logical thinking. Due to the importance of practicing the construction of scientific texts, our aim was to examine the scholarly outputs generated within the framework of teaching and learning through concept mapping, with a focus on uncovering indications of empowerment in the exploration of underrepresented zoological taxa. The present research followed the methodology of content analysis to examine publications developed by students together with the authors of this writing and associated researchers. Specifically, productions that used the conceptual integration tool to elucidate the taxonomic, phylogenetic and ecological contents of neglected fauna groups were selected for analysis. Our examination of these documents reveals that active student involvement is stimulated through the exploration of abstract concepts pertaining to enigmatic invertebrates, providing the development of scientific writing skills in the realm of biodiversity studies. Such experiences serve as evidence of empowerment within higher education, while also fostering a deeper sense of belonging to biological diversity and its environmental interrelations.